NANOEMULSION OF OKRA FRUIT EXTRACT AS ANTIDIABETIC TREATMENT - DJAMIL, RATNA; ZAIDAN, SARAH; RAHMAT, DENI; PRATAMI, DIAH KARTIKA; HAKIM, FELIX (International Journal of Applied Pharmaceutics, 2020)
Objective: Okra (Abelmoschus esculentus (L.) Moench) has potential antidiabetic activity. This study created a nanoemulsion of okra extract (NOE) and examined its activity on alloxan-induced diabetes mellitus in mice. Methods: Okra was macerated with 70% ethanol and dried in a rotary evaporator into the crude extract. The extract was encapsulated in a solution of glyceryl caprylate, propylene glycol, and glycerine to form a nanoemulsion. To determine the antihyperglycaemic effect of okra extract, 35 male mice (Mus musculus L.) were divided into seven groups: a non-diabetic normal control group and six diabetic mice groups (untreated negative control, glibenclamide-treated positive control, and four treatments with okra ethanol extract (OEE) at 200 and 400 mg/kg BW and NOE at 200 and 400 mg/kg BW). Results: The group treated with NOE at 400 mg/kg BW (NOE400) had the lowest average blood glucose level of 93.4 mg/dL among hyperglycaemic mice. The decrease in blood glucose levels in NOE400 (52.05%) was significantly different from those in the positive control (42.63%) and OEE treatments (39.32%). The nanoemulsion used in this study fulfills quality requirements, with a mean particle size of 134.7 nm, a polydispersity index of 0.512, and a zeta value of −26.72 mV. Conclusion: NOE reduced blood glucose levels in alloxan-induced hyperglycaemic mice better than OEE. Nanoemulsion can improve the antidiabetic activity of okra extract by increasing penetration of active compounds into interstitial space so that their delivery and bioavailability are higher.